2004
DOI: 10.1007/s10151-004-0147-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of local stage in rectal cancer using endorectal ultrasonography (EUS)

Abstract: EUS is a valuable diagnostic tool in local staging of rectal cancer. Progressively increasing experience will overcome the obstacles in accurate interpretation of ultrasound images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In our study, we overstaged four T2 tumors, and these were probably related to artifacts from tissue edema or inflammation. Consistent with other literature results, our study showed that ERUS was 86% accurate in assessing rectal wall penetration [4,[6][7][8][9][10][11][12][13][14][15][16][17][18]. In our results, a learning curve for T staging was not apparent.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, we overstaged four T2 tumors, and these were probably related to artifacts from tissue edema or inflammation. Consistent with other literature results, our study showed that ERUS was 86% accurate in assessing rectal wall penetration [4,[6][7][8][9][10][11][12][13][14][15][16][17][18]. In our results, a learning curve for T staging was not apparent.…”
Section: Discussionsupporting
confidence: 92%
“…As revealed by our results, 60% of our patients underwent ERUS concurrently during the same colonoscopic session. With reported accuracy rates of 69-92%, ERUS is believed to be the most accurate investigative choice in determining depth of rectal tumor invasion [4,[6][7][8][9][10][11][12][13][14][15][16][17][18]. Accurate tumor staging is important in selecting patients for possible multimodality treatment including preoperative chemoradiation, which may be beneficial in locally advanced tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported on the accuracy of ERUS (Table 1). 10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Despite a wide range of results, common patterns have emerged. One is that the accuracy of ERUS T-staging varies in relation to tumor stage; ERUS tends to be least accurate in assessing intramural T2 masses, which are often overstaged.…”
Section: Staging Accuracymentioning
confidence: 99%
“…Previous studies of ERUS have reported T-staging accuracy between 60 and 90% [22,23] and N-staging accuracy between 59 and 82% [24,25]. Meta-analysis of tumour staging demonstrates sensitivity results for T1, T2, T3 and T4 stages of 87, 80, 96 and 95%, respectively.…”
Section: Discussionmentioning
confidence: 82%